Association between psychological health and wound complications after surgery. Issue 6 (14th February 2017) - Britteon, P; Cullum, N; Sutton, M
Abstract: Background: Surgical wound complications remain a major cause of morbidity, leading to higher costs and reduced quality of life. Although psychological health is widely considered to affect wound healing, the evidence on wound outcomes after surgery is mixed. Studies generally focus on small samples of patients undergoing a specific procedure and have limited statistical power. Methods: This study investigated the relationship between three different measures of anxiety and/or depression and seven adverse surgical outcomes using observational data collected before and after surgery between 2009 and 2011. A wide range of confounding factors was adjusted for, including patient demographics, physical co-morbidities, health-related behaviours, month of operation, procedure complexity and treating hospital. Results: The estimation sample included 176 827 patients undergoing 59 410 hip replacements, 64 145 knee replacements, 38 328 hernia repairs and 14 944 varicose vein operations. Patients with moderate anxiety or depression had an increased probability of wound complications after a hip replacement (odds ratio (OR) 1·17, 95 per cent c.i. 1·11 to 1·24). They were more likely to be readmitted for a wound complication (OR 1·20, 1·02 to 1·41) and had an increased duration of hospital stay by 0·19 (95 per cent c.i. 0·15 to 0·24) days. Estimated associations were consistent across all four types of operation and for each measure of anxiety and/or depression. Conclusion: Preoperative psychological health is a significant risk factor for adverse wound outcomes after surgery for four of the procedures most commonly performed in England. Abstract : Anxious and depressed patients get more complications